The Effect of the Outing Class Method on Student Activeness in IPAS of Grade V at SDN Inpres Tanjung Baru - Rufi'ah; Hairunisa; Sri Hardiningsih Hanafi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The objective of this research is to gain an understanding of the effectiveness of the outing class method before and after its implementation in enhancing student engagement in IPAS (Integrated Natural and Social Sciences) learning among fifth-grade students at SDN Inpres Tanjung Baru. The study involved a total of 18 fifth-grade students as research subjects. This study utilized a quantitative method through a quasi-experimental design method with a One Group Pretest-Posttest Design. Data analysis included descriptive statistics, normality distribution tests, and hypothesis testing using a paired T-Test. Descriptive analysis indicated an increase in the average score from 65.94 (pretest) to 119.22 (posttest). The normality test using the Kolmogorov–Smirnov method produced a significance value of 0.200 (p > 0.05) for both pretest and posttest data, supported by the Shapiro–Wilk test, which yielded significance values of 0.671 (p > 0.05) for the pretest and 0.743 (p > 0.05) for the posttest. Furthermore, the hypothesis test using the Paired Sample T-Test yielded a significance value of 0.000 (p < 0.05), Showing a meaningful statistical difference between the pretest and posttest results. Therefore, it can be concluded that the outing class method has a significant impact on improving student engagement in IPAS learning.